COGNITIVE-COMMUNICATIVE- ACTIVITY-BASED APPROACH TO TEACHING STUDENTS OF NON-LANGUAGE HIGH SCHOOL IN PROFESSIONAL FOREIGN LANGUAGE SPEECH ACTIVITY - Elena A. Karabutova; Lyudmila N. Kolchintseva (Moscow Polytechnic University, 2016)
This paper deals with the problem of teaching students of nonBlanguage high schools in foreign language speech activity from the point of psycholinguistic and lingvodidactic research, touching cognitive, activityBbased and communicative aspects of speech of an individual, who is able to perceive the other's speech and formulate his thoughts, discussing issues of the future career.